Chinese Adolescents’ Reading Motivation Profiles and Their Relations to Reading Amount - Wang, Xiaocheng; Jin, Yuanying; Jia, Lina (Frontiers in Psychology, 2022)
This study used a person-centered approach to identify reading motivation profiles of 514 Chinese adolescents in seventh- to ninth- grade, based on dimensions of intrinsic reading motivation (curiosity and involvement) and extrinsic reading motivation (grades and competition). Furthermore, the effects of each profile on outcome variables (reading amount for enjoyment and for school) were investigated. Latent profile analyses revealed three reading motivation profiles: high quantity (high on all four dimensions), high intrinsic (high on curiosity and involvement, low on grades and competition), and moderate quantity (moderate on all four dimensions). The high-intrinsic and high-quantity profiles proved to be equally successful in terms of amount of reading for enjoyment and for school, and both significantly exceeded the moderate-quantity profile. The current findings emphasize the importance of intrinsic reading motivation and the importance of quality of motivation, compared with its quantity.